Adaptation options for agricultural cultivation systems in the South Central Coast under the context of climate change: Assessment Report. - Bo, Nguyen Van; Hoanh, Chu Thai; Du, Pham Van; Cuong, Ho Huy; Hanh, Tran Thi My; Tuan, Duong Minh; Trung, Nguyen Duc (2019)
This report highlights the results of consultation meetings and field visits organized by the Department of Crop Production and the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia in association with the three offices of the Department of Agriculture and Rural Development in the South Central Coast provinces of Binh Thuan, Ninh Thuan, and Khanh Hoa, in combination with consultation with the provinces in the conference: “Summing up crops production in the Winter-Spring season in 2018-2019, implementing the Summer-Autumn season, Main rice season in 2019 for the South Central Coast and the Central Highlands” held by the Ministry of Agriculture and Rural Development in Tam Ky City, Quang Nam Province on 12 April 2019. The meetings underlined the progress made by the provinces on climate change adaptation and mitigation, options for risk reductions in agricultural production, and conversion of crop structure as results of implementing the guidelines of the provinces and the Sector, especially, solutions for reservation and efficient and economic use of water under the context of climate change. This assessment report also reviews some issues related to the agricultural transformation of the region in adapting to risks caused by climate change. They are based on comparative advantages in terms of geographical location and market of key agricultural products. This report also points out shortcomings in using land and unreasonable points in managing and using important natural resources, especially water, and provides recommendations for the agricultural transformation and inter-regional connection with the Central Highlands and the Southeast. The team also introduces climate-related risks maps and adaptation plans (CS MAP) which is applied in the five provinces in the Mekong Delta Region, and hopes this solution’s expansion shall be supported by the Ministry of Agriculture and Rural Development and the provinces.